PENGEMBANGAN MODUL MATA KULIAH PKAKTIK BIMBINGAN DAN KONSELING BELAJAR BAGI MAHASISWA JURUSAN PPB/BK FIP UNIMED - Mirza Irawan; Nani Barorah Nurarjani; Nindya Ayu Pristanti (Universitas Negeri Medan, 2019)
This study aimed to: (1) Develop Module as learning media on academic guidance and counseling practice subject in Guidance and Counseling Department, Faculty of Education, Medan State University (2) Test the feasibility of module as learning media on academic guidance and counseling practice subject with content experts, media experts and respondent. This research is a research and development followed the 4-D Models method, namely (1) Define, (2) Design, (3) Development, (4) Disseminate. The data collection method involved two content experts and two learning media experts. Product quality testing was conducted on 20 students academic year 2018 of Guidance and Counseling Department, Faculty of Education, Medan State University. Data analysis techniques for the feasibility of learning media using qualitative descriptive analysis.Keywords: Module, Academic Guidance and Counseling Practice